Engineering highly aligned continuous nanofibers via electrospinning: A comprehensive study on collector design, electrode geometry, and collector speed - Mehmet Selim Demirtaş; Mrinal C. Saha (eXPRESS Polymer Letters, 2024)
Nanomaterials, particularly nanofibers produced through electrospinning, have garnered significant attention due to their unique properties and diverse applications. This research explores the influence of collector design, electrode geometry, and collector speed on the properties of electrospun polyacrylonitrile (PAN) nanofibers. Finite element analysis (FEA) was employed to simulate electric fields, revealing the impact of collector geometry on field intensity. The experimental setup, enclosed in an isolated chamber, employed various collector types and electrode configurations. Scanning electron microscope (SEM) analysis showcased the effect of collector speed on fiber alignment and diameter. Furthermore, FEA simulations elucidated the role of electrode geometry and voltage in shaping the electric field, impacting fiber properties. The study introduces a novel, in-house method for producing highly aligned nanofibers and provides insights into optimizing electrospinning parameters for enhanced fiber properties. A testing protocol is devised to minimize surface damage when conducting mechanical tests on nanofiber films, employing a dynamic mechanical analyzer (DMA). Mechanical testing demonstrated the correlation between alignment and tensile strength. Overall, this research contributes valuable insights for tailoring electrospinning processes for tissue engineering and energy storage.